2014
DOI: 10.3109/13880209.2014.910236
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical properties of dietary plants extracts: Prevention of diabetic nephropathy through inhibition of glycation and toxicity to erythrocytes and HEK293 cells

Abstract: Context: Glycated albumin is reported to elicit pathobiologic effects in diabetic nephropathy and abrogating its biologic effects has novel therapeutic potential. Objective: This study examines the effects of dietary plants extracts (Laurus nobilis, Carum carvi, Coccinia grandis, Mentha arvensis, Phaseolus vulgaris) against albumin glycation and its toxicity to erythrocytes and HEK293 cells. Materials and methods: Albumin (10 mg/ml) was incubated with fructose (250 mM) in PBS along with aqueous plant extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…It was observed that CGF extract showed significant inhibition to amyloid aggregation during the course of experiment, 7–28 days, indicating their potential to prevent conformational changes in albumin during glycation. The reason behind decrease in β-amyloid formation may be the low-molecular-weight bioactive compounds such as polyphenols, phenolic acids or flavonoids present in the extract which have anti-amyloidogenic effects 49 . The results of this study corroborate the effective antiglycation action of CGF extract as they not only counteracted with the initial glycation reaction and its progression but also prevented amyloid cross β-structures in BSA in vitro .…”
Section: Discussionsupporting
confidence: 70%
“…It was observed that CGF extract showed significant inhibition to amyloid aggregation during the course of experiment, 7–28 days, indicating their potential to prevent conformational changes in albumin during glycation. The reason behind decrease in β-amyloid formation may be the low-molecular-weight bioactive compounds such as polyphenols, phenolic acids or flavonoids present in the extract which have anti-amyloidogenic effects 49 . The results of this study corroborate the effective antiglycation action of CGF extract as they not only counteracted with the initial glycation reaction and its progression but also prevented amyloid cross β-structures in BSA in vitro .…”
Section: Discussionsupporting
confidence: 70%
“…In our study, we only tested the survival rate of cells, but from the results obtained by Tupe et al . [ 24 ] we can presume that the other parameters are likely to correspond to the previous study.…”
Section: Discussionsupporting
confidence: 52%
“…Its antiglycative properties were confirmed previously in several reports on such medicinal herbs as Salvia sp., Melissa officinalis, Mentha spicata , and other Lamiaceae. [ 23 24 25 ] The numerous other bioactivities have been also reviewed. [ 1 26 ] However, the ability of a rosmarinic acid-rich extract to protect mammalian cells against damage induced by glycated albumin has not been reported, yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional molecules that are present in natural compounds are responsible for their curative potential. Culinary herbs with high polyphenol content and antioxidant activity represent promising approach (Tupe et al 2013b(Tupe et al , 2015b. Recent studies have shown the beneficial effects of medicinal plants and bioactive compounds in AGEs mediated pathogenesis using experimental diabetic animal models (Elosta et al 2012;Sadowska-Bartosz & Bartosz 2015;Younus & Anwar 2016).…”
Section: Introductionmentioning
confidence: 99%